Third Annual Fresno County Young Lawyers Hopper Luncheon with Justice Allen Broussard - Watkins, Howard::::::::: (1984)
Close up of California Associate Justice Allen Broussard speaking at lectern Luncheon at Golden State Plaza ballroom